New Data on Breeding Strategies and Reproductive Success of the Globally Threatened Turtle Dove Co-Occurring with the “Competitive” Collared Dove and the “Predatory” Maghreb Magpie in Olive Orchards - Wafae Squalli; Ismail Mansouri; Driss Ousaaid; Mohammed Hmidani; Hamid Achiban; Fatima Fadil; Mohamed Dakki (International Journal of Zoology)
Interactions between co-occurring species, including competition and predation, comprise critical processes regulating local community structure, habitat use, and diversity. We monitored nesting habitats, breeding chronology, and reproductive success rates to describe the patterns of spatiotemporal organization of three co-habiting species: the “native” turtle dove, the “invasive” collared dove, and the “predatory” Maghreb magpie. We defined nesting site parameters, breeding chronology dates, and success rates to explain how these species are dispersed in space and time. Similarly, predation attacks were evaluated. Patterns of habitat use were best explained by fear of predation and competition. Both doves selected nesting sites far away from the predatory Magpie to protect their nests. Equally, sympatric Columbidae turtle dove and collared dove were segregated horizontally and vertically only in space to reduce competition inside olive orchards. On the other side, Maghreb magpie started the breeding activity first, most probably to benefit from food abundance targeted in doves’ nests (eggs and nestlings). Further, breeding success was higher in both doves, despite predation pressure exercised by the Magpie and other reptiles. Magpie nests were colonized by the great spotted cuckoo (Clamator glandarius). Finally, this study provides the first and only detailed data on nest-niche of the turtle dove co-occurring with competitor and predator species, in the entire Northwest Africa range. Additionally, our data provide an opportunity of large-scale comparative studies of the nesting niche and breeding performances of the turtle dove, collared dove, and Maghreb magpie complex.